1993
DOI: 10.1038/jcbfm.1993.90
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin Decreases the Contractile Responses of the Porcine Basilar Artery to Vasoactive Substances

Abstract: Summary: The effects of endotoxin (lipopolysaccharide; LPS) on the reactivity of isolated porcine basilar artery were examined using in vitro tissue bath techniques. The active muscle tone of the basilar arterial rings with or without endothelial cells induced by U46619 (1 fl-M) reached a plateau in 15 min, which was stable for the first hour and gradually decreased during the next 5 h. This time-dependent decrease in tone was significantly poten tiated in the presence of LPS (20 fl-g/ml). Gram-negative bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 39 publications
3
10
0
Order By: Relevance
“…In addition, others have reported that dexamethasone does not alter constrictor or dilator responses in vessels. 42,43 These data strengthen the concept that TNF␣-induced vasodilatation of cerebral arterioles is due entirely to NO production from inducible NO synthase.…”
Section: Tnf␣ and Inducible No Synthasesupporting
confidence: 66%
“…In addition, others have reported that dexamethasone does not alter constrictor or dilator responses in vessels. 42,43 These data strengthen the concept that TNF␣-induced vasodilatation of cerebral arterioles is due entirely to NO production from inducible NO synthase.…”
Section: Tnf␣ and Inducible No Synthasesupporting
confidence: 66%
“…95 - 96 A recent study suggests that induction of NO synthase also occurs in response to lipoporysaccharide in cerebral vascular muscle in vitro. 97 This induction was associated with impaired responses of cerebral arteries to vasoconstrictor stimuli. 97 Preliminary evidence suggests that lipopolysaccharide produces marked dilatation of cerebral arterioles in vivo, which is dependent on formation of NO and may be mediated by induction of NO synthase.…”
Section: Inducible Nitric Oxide Synthasementioning
confidence: 99%
“…38 Others have reported that dexamethasone does not alter constrictor or dilator responses of cerebral and extracerebral vessels. 39,40 Dexamethasone does not affect the activity of COX-1 in vivo. 41 Thus, it is unlikely that dexamethasone reduced LPS-induced dilatation by a nonspecific effect on vascular tone.…”
Section: Cox-2 Expression In Brainmentioning
confidence: 99%